Aligning Physical Literacy With Critical Positive Youth Development and Student-Centered Pedagogy: Implications for Today's Youth - Santos, Fernando; Newman, Tarkington J.; Aytur, Semra; Farias, Claudio (Frontiers in Sports and Active Living, 2022)
The purpose of this article is three-fold: (1) revisit the concept of life skills to position physical literacy as a social justice life skill; (2) make the argument that physical literacy is particularly relevant within a critical positive youth development perspective; and (3) propose a novel critical praxis for developing physical literacy amongst youth. When considering emergent social issues, youth programming has the potential to integrate concepts from a range of theoretical frameworks, which may help youth transform into social change activists and competent movers. Such critical perspectives may guide sport and physical education programming as contemporary society poses numerous challenges concerning youths' diverse emotional, mental, physical, and social needs. In order to advance knowledge and practice, we urge researchers and practitioners to rethink the way sport and physical education has been traditionally conceptualized. Ultimately, we propose that educating individuals to recognize and then confront neoliberal values within a post-pandemic landscape is critical. These notions may help researchers (re)frame their positionality and readiness to tackle physical literacy through broader theoretical lenses which—as alluded to in this article—may equip practitioners and researchers to meaningfully advance social justice.